The postcard in Spain: uses and trends - López Hurtado, Mariana (Revista General de Información y Documentación, 2013)
Since the birth of the postcard in 1869 the uses that have been attributed to it have varied over time, reaching to consolidate an important publishing industry and a great popularity among citizens. However, there is not any study that show the current use that these documents have in Spain and that show the appreciation and opinion that Spanish have of them. For this reason an objective study is presented in which these issues are clarified and glimpse an assessment of the postcard highlighting its value as a mean of communication and as a collectible document.